O trabalho de Mendel: um caso de prematuridade científica? - Batisteti, Caroline Belotto [UNESP]; Araujo, Elaine Sandra Nicolini Nabuco de [UNESP]; Caluzi, João José [UNESP] (My University, 2010)
This study aims to discuss the idea of scientific prematurity, proposed by Gunther S. Stent, as applied to Mendel’s work. According to Stent “A discovery is premature if its implications cannot be connected to a series of simple logical steps to canonical contemporary knowledge (or generally accepted). One of the main elements considered by Stent to classify a “discovery” as premature concerns its lack of appreciation in its own time. He considered Mendel’s discovery on the “particulate nature of heredity” as being premature. However this idea has received some criticism. One of them refers to the fact that those who advertised Mendel’s work in the early 20th century used a terminology which was not found in the original article. Such approach undermines the equivalence and retrospective recognition, which support the concept of prematurity. Taking into account the focus of our study, we also discuss how the concept of prematurity is related to Whiggism.

O presente estudo tem por objetivo discutir a idéia de prematuridade científica, proposta por Gunther S. Stent, em relação ao trabalho de Mendel. Segundo Stent uma descoberta é prematura se as suas implicações não puderem ser conectadas por uma série de etapas lógicas simples ao conhecimento canonico contem porâneo (ou geralmente aceito). Um dos principais elementos considerados por Stent ao classificar uma descoberta como permatura diz respeito à não apreciação deste em sua época. Ele considerou a descoberta de Mendel sobre a natureza particulada da hereditariedade prematura. No entanto essa idéia recebeu criticas. Uma delas refere-se ao fato de os divulgadores do trabalho de Mendel terem utilizado uma terminologia que não está presente no artigo original, o que comprometeria a equivalência e reconhecimento retrospectivo, suportes do conceito de prematuridade. Tendo em vista nosso foco de estudo, disuctiremos também de que forma o conceito de prematuridade nos remete ao whiguismo.
Mendel’s work: a case of scientific prematurity?
Keywords: Scientific prematurity; Gregor Mendel; Whiggism; Prematuridade científica; Gregor Mendel; Whiguismo